Aberrant dynamic minimal spanning tree parameters within default mode network in patients with autism spectrum disorder - Jia, Huibin; Wu, Xiangci; Wu, Zhiyu; Wang, Enguo (Frontiers in Psychiatry, 2022)
The altered functional connectivity (FC) level and its temporal characteristics within certain cortical networks, such as the default mode network (DMN), could provide a possible explanatory framework for Autism spectrum disorder (ASD). In the current study, we hypothesized that the topographical organization along with its temporal dynamics of autistic brain measured by temporal mean and variance of complex network measures respectively were significantly altered, which may further explain the autistic symptom severity in patients with ASD. In order to validate these hypotheses, the precise FCs between DMN regions at each time point were calculated using the resting-state functional magnetic resonance imaging (fMRI) datasets from the Autism Brain Imaging Data Exchange (ABIDE) project firstly. Then, the minimal spanning tree (MST) technique was applied to construct time-varying complex network of DMN. Through analyzing the temporal mean and variance of MST parameters and their relationship with autistic symptom severity, we found that in patients with ASD, the information exchange efficiencies between cortical regions within DMN were significantly lower and more volatile compared with those in typical developing participants. Moreover, these alterations within DMN were closely associated with the autistic symptom severity of the ASD group.